2018
DOI: 10.1111/rec.12715
|View full text |Cite
|
Sign up to set email alerts
|

Seeding tallgrass prairie in monospecific patches promotes native species establishment and cover

Abstract: In tallgrass prairie reconstruction, the way desired seeds are arranged on the landscape may affect species establishment, species persistence, and the establishment and persistence of undesired (nonseeded) species from the local propagule pool. To test effects of species seeding pattern on how grasslands develop spatially, we seeded 20—4 × 4–m bare soil plots with 16 tallgrass prairie species. Treatment plots were divided into 16—1 × 1–m subplots, 64—0.5 × 0.5–m subplots, 256—0.25 × 0.25–m subplots, or 1,024—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…As in other studies (Dickson & Busby, ; Kordbacheh, Jarchow, English, & Liebman, ; Nemec, Allen, Helzer, & Wedin, ; Seahra et al, ), a productive Heliantheae forb initially dominated our experimental tallgrass prairies reconstructed on a former agricultural field. To address this statistically, we allowed diversity effects in our DI models to differ in H. maximiliani plots and treated these plots with a different variance structure.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As in other studies (Dickson & Busby, ; Kordbacheh, Jarchow, English, & Liebman, ; Nemec, Allen, Helzer, & Wedin, ; Seahra et al, ), a productive Heliantheae forb initially dominated our experimental tallgrass prairies reconstructed on a former agricultural field. To address this statistically, we allowed diversity effects in our DI models to differ in H. maximiliani plots and treated these plots with a different variance structure.…”
Section: Discussionsupporting
confidence: 76%
“…This is useful when considering to what extent plant species fine-scale spatial relationships affect plot-scale diversity effects. Plant species interact on finite-scales, and if their interaction distances are small enough, their spatial relationships can presumably affect the interactions they experience and respond to (Houseman, 2014;Lamošová, Doležal, Lanta, & Lepš, 2010;Murrell, 2010;Porensky, Porensky, Vaughn, & Young, 2012;Seahra, Yurkonis, & Newman, 2019;Stoll & Prati, 2001;Yurkonis & McKenna, 2014). In spatially manipulated tallgrass prairies, increasing species interspecific interactions increased biomass and favored clonal forbs (McKenna & Yurkonis, 2016), an effect that was replicated by seeding species in smaller conspecific patches (Seahra, Yurkonis, & Newman, 2016).…”
mentioning
confidence: 99%
“…Despite the difficulties of seedling establishment in early restoration due to these stresses, our findings emphasize the importance of adding seeded species early in the process before competitively dominant species reach high cover. For the integration of target species which, as in our case, do not establish when seeded early nor are likely to establish when seeded in later, other approaches might be necessary, such as creating microhabitats, creating weeded monospecific patches, or selectively transplanting adult specimens (Drayton & Primack 2000;Seahra et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Another study by Seahra et al (2019) identified competition as a bottleneck to species establishment by comparing species performance when they were sown alone versus in mixtures with other species. Most of the studied target species showed greater establishment when sown alone than in mixtures.…”
Section: Competitionmentioning
confidence: 99%